Metabetaeus lapillicola, a new species of alpheid shrimp (Decapoda: Caridea) from Japan, inhabiting unusual pebble beaches - Yamashita, Ryunosuke; Komai, Tomoyuki; Kon, Koetsu (Zootaxa, 2023)
The alpheid shrimp genus Metabetaeus Borradaile, 1899 was previously known from two species associated with anchialine pools and caves, M. minutus (Whitelegge, 1897) and M. lohena Banner & Banner, 1960, and one species inhabiting in coral reef, M. mcphersonae Anker, 2010. In this study, a new species of the genus is described based on fourteen specimens collected from Shizuoka and Mie Prefectures, Honshu, central Japan. Metabetaeus lapillicola n. sp. inhabits interstitial spaces among small pebbles deposited in lower intertidal to upper subtidal zone, representing rather unusual habitat not only for Metabetaeus, but even for carideans. It is distinguished from three congeneric species by the presence of a pterygostomial spine on the carapace, greatly unequal chelipeds with the major one being substantially elongate, and the lack of a distinct distolateral spine on the uropodal endopod. Phylogenetic analyses using the mitochondrial 16S rRNA and COI genes support the recognition of the new species. The generic diagnosis of Metabetaeus is emended to accommodate the new species.